Multidisciplinary therapy including proton beam radiotherapy for a Ewing sarcoma family tumor of maxillary sinus in a 4‐year‐old girl. Issue 12 (16th October 2013) - Yamaoka, Masayoshi; Akiyama, Masaharu; Yokokawa, Yuichi; Terao, Yoko; Yokoi, Kentaro; Kato, Takakuni; Fukushima, Takashi; Sakurai, Hideyuki; Ida, Hiroyuki; Andersen, Peter
<x xml:space="preserve">Abstract</x> Background Although complete resection offers the best chance for controlling head and neck Ewing sarcoma family tumors (ESFTs), it is occasionally unfeasible because of possible functional and cosmetic side effects. Planning multidisciplinary treatment for head and neck ESFT is challenging. Methods and Results A 4‐year‐old girl had left‐sided excessive tearing, nasal obstruction, and exophthalmos for 4 months. A CT scan showed a mass filling the left maxillary sinus and extending to the left orbital wall. After a diagnosis of ESFT was established with biopsy, the patient was treated with vincristine, doxorubicin, cyclophosphamide/ifosfamide etoposide (VDC/IE) regimen over 50 weeks; partial maxillectomy was performed at week 15 and was followed by proton radiotherapy. The patient has remained tumor‐free for 16 months, with preservation of facial form and function. Conclusion Partial resection combined with proton radiotherapy may enable maximal tumor control and minimal functional and cosmetic side effects in children with head and neck ESFT. © 2013 Wiley Periodicals, Inc. Head Neck 35: E386–E390, 2013